Peningkatan Hasil Belajar Siswa Tunanetra Kelas V SLB-A Yaketunis Yogyakarta dengan Menggunakan Media “ASIK” - K Kustanti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
This classroom action research was conducted to overcome problematic thematic learning outcomes in limited face-to-face learning for blind students at SLB Yaketunis Yogyakarta. This study uses a classroom action research approach. The research design uses the Kurt Lewin Model with two cycles where each cycle consists of four stages of activity: planning, implementation, observation/observation, and reflection. Each cycle was carried out and completed in two meetings. Data collection techniques are carried out through tests, compliance, and documentation. Data analysis was carried out using a quantitative descriptive approach. Based on the results of the study, it can be concluded that (1) students' interest and motivation in thematic learning activities using the scientific method approach, which utilizes Asik audio with thematic content, can have a positive impact on blind students so that learning outcomes increase in each cycle; (2) students are more active in responding to the teacher's stimulus in learning as evidenced through performance responses.